2020
DOI: 10.1101/2020.01.14.904755
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single molecule mass photometry of nucleic acids

Abstract: Mass photometry is a recently developed methodology capable of detection, imaging and mass measurement of individual proteins under solution conditions. Here, we show that this approach is equally applicable to nucleic acids, enabling their facile, rapid and accurate detection and quantification using sub-picomoles of sample. The ability to count individual molecules directly measures relative concentrations in complex mixtures without need for separation. Using a dsDNA ladder, we find a linear relationship be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The resulting images consist of diffraction-limited spots with a ratiometric contrast value in the range of 0.001ā€“0.1 ( Figure 1 ). The number of particles binding to the glass surface over a given time interval is proportional to the particle concentration, whereas the particle contrast is proportional to the mass for a variety of biological particles, such as proteins, 32 DNA, 33 molecular machines, 34 antibodies, 35 protein cages, 36 and virus capsids 29 (see Figure S15 for contrast to mass calibration). At this stage, quantitative conversion of ratiometric contrast to particle size is not possible, however, previous studies of lipid nanodiscs showed that changes in lipid mass can be accurately quantified.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The resulting images consist of diffraction-limited spots with a ratiometric contrast value in the range of 0.001ā€“0.1 ( Figure 1 ). The number of particles binding to the glass surface over a given time interval is proportional to the particle concentration, whereas the particle contrast is proportional to the mass for a variety of biological particles, such as proteins, 32 DNA, 33 molecular machines, 34 antibodies, 35 protein cages, 36 and virus capsids 29 (see Figure S15 for contrast to mass calibration). At this stage, quantitative conversion of ratiometric contrast to particle size is not possible, however, previous studies of lipid nanodiscs showed that changes in lipid mass can be accurately quantified.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Existing techniques are very powerful, and have enabled and continue to yield detailed information on sample composition and heterogeneity. Key to MP is the combination of speed and simplicity, as well its broader capabilities, which include detection of small ligand binding 7 , quantitative evaluation of binding affinities and kinetics in a surface free manner 10,33 , nucleic acid interactions 34 and more general capabilities for characterising sample heterogeneity 9 . All of these measurements are performed in the same way as the ones presented herein: by adding small volumes (Āµl) of low concentration (<ĀµM) unlabelled samples in a buffer of choice to a microscope cover slide.…”
Section: Discussionmentioning
confidence: 99%
“…This range will enable measurements up to 100 mm affinities, making MP a powerful approach for characterizing biomolecular interactions without labels and single-molecule sensitivity in a minimally perturbative fashion. Furthermore, the applicability of MP to both nucleic acids [33] and large multimolecular machines [34] provides scope for MP becoming a universal tool for studying biomolecular interactions and dynamics in a rapid, label-free, yet single-molecule-sensitive fashion.…”
Section: Understandinghowbiomoleculesinteractwitheachotherismentioning
confidence: 99%